Answer:
<em>x² - 28x√x + 294x - 1372√x + 2404 </em>
Step-by-step explanation:
f(x) =
+ 3
g(x) = x - 7
h(x) = √x
f(g(h(x))) - ?
g(h(x)) = √x - 7
f(g(h(x))) =
+ 3 = ( √x - 7 )² × ( √x - 7 )² + 3 =
= (x - 14√x + 49)(x - 14√x + 49) + 3 =
= x² - 14x√x + 49x - 14x√x + 196x - 686√x + 49x - 686√x + 2401 + 3 =
= <em>x² - 28x√x + 294x - 1372√x + 2404</em>
Answer:
65mph
Step-by-step explanation:
Answer:
$8
Step-by-step explanation:
14 - 6 = 8
Answer: The common ratio is -1/3
-----------------------------------------------------------
Work Shown:
Pick any term to divide it by the previous term. I'm going to pick the second term and divide it by the first term.
r = common ratio
r = (term 2) divided by (term 1)
r = (4/9) divided by (-4/3)
r = (4/9) * (-3/4)
r = (4*(-3))/(9*4)
r = -12/36
r = -1/3
The common ratio is -1/3
This means you multiply each term by -1/3 to get the next term
For instance
term 2 = r*(term 1)
term 2 = (-1/3)*(-4/3)
term 2 = ((-1)*(-4))/(3*3)
term 2 = 4/9
Answer:
I've done this question: Its batch 5
Step-by-step explanation:
It has to be all equal proportions